Reconfiguration of 25 kW Solar PV Power Plant (International Journal of Engineering and Computer Science, 2017)
Power is one of the most critical components of infrastructure resolvent for the economic growth and welfare of nations. The development of sufficient infrastructure is essential for sustained growth of the Indian economy. . Electricity demand in the country has increased rapidly due to the fast growing industries and population growth. Solar play major role to meet the increasing demand. A 25 kW grid-connected photovoltaic (PV) power generation system was installed and monitored at the Kamaraj College of Engineering and Technology in Virudhunagar since March 2014. In this project work the various factors that affect the performance of the solar PV are analyzed. The solar PV panels installed here are mono crystalline, poly crystalline and low concentrated PV modules. Each PV panels are connected in series or parallel. In this PV plant several modules are get damaged due to the abnormal weather condition and some panels are in good working condition. The only solution of this problem is the rearrangement of solar PV panels. By doing reconfiguration, the performance of the solar plant should be improved and also it improves the reliability and reduces the vulnerability to power loss by damage.